2010
DOI: 10.1158/0008-5472.can-09-1872
|View full text |Cite
|
Sign up to set email alerts
|

Smad Signaling Is Required to Maintain Epigenetic Silencing during Breast Cancer Progression

Abstract: Breast cancer progression is associated with aberrant DNA methylation and expression of genes that control the epithelial-mesenchymal transition (EMT), a critical step in malignant conversion. Although the genes affected have been studied, there is little understanding of how aberrant activation of the DNA methylation machinery itself occurs. Using a breast cancer cell-based model system, we found that cells that underwent EMT exhibited overactive transforming growth factor β (TGFβ) signaling and loss of expre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 38 publications
4
133
1
Order By: Relevance
“…The function of the encoded protein, cingulin remains elusive; however it appears to be important for junction formation and also negatively regulates cell proliferation (45). Additionally, CGN is downregulated during the epithelial-mesenchymal transition in breast cancer model cells (46). These previous findings indicate that cingulin may suppress tumor development, in accordance with the results of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…The function of the encoded protein, cingulin remains elusive; however it appears to be important for junction formation and also negatively regulates cell proliferation (45). Additionally, CGN is downregulated during the epithelial-mesenchymal transition in breast cancer model cells (46). These previous findings indicate that cingulin may suppress tumor development, in accordance with the results of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…Epigenetic gene silencing has also been indicated to correlate with EMT processes (Dumont et al, 2008;Song et al, 2010), and recent studies reported that the TGFb-TGFbR-Smad2 signaling axis maintains the epigenetic silencing of critical EMT genes, and so is relevant to cancer progression, through a modulating in the DNA-binding activity of DNA methyltransferase DNMT1 (Papageorgis et al, 2010). In the present study, we first performed (1) the classification of epithelial-like or mesenchymal-like OSCC cell lines based on expression profiles of typical EMT-related genes and (2) the expression-based and methylation-based screening of novel EMT-related genes in the Wnt signaling pathway using a panel of classified OSCC cell lines, resulting in the identification of WNT7A and WNT10A silenced by mesenchymalspecific DNA hypermethylation in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the induction of EMT was accompanied by de novo DNA methylation of promoter regions around several genes, including E-cadherin, estrogen receptor, and TWIST, and interestingly, the repression of E-cadherin transcription preceded the subsequent acquisition of methylated CpG sites (Dumont et al, 2008). Most recently, the TGFb-TGFbR-Smad2 signaling axis was revealed to maintain epigenetic silencing of critical EMT genes and cancer progression through modulating the DNA-binding activity of a DNA methyltransferase, DNMT1 (Papageorgis et al, 2010). In addition, the demethylation of FOXA1/2 was described to reactivate E-cadherin expression in a pancreatic cancer cell line, Panc1 (Song et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, others made contrary findings in gastric carcinoma cells in culture and in a breast carcinoma xenograft model (Tang et al 2007;Ehata et al 2011). TbRISmad2 signaling has been implicated in maintaining epigenetic silencing that promotes and sustains EMT and the CSC phenotype (Papageorgis et al 2010). Even in hematological malignancies, in which TGF-b has a predominantly tumor suppressive role, TGF-b signaling supports leukemia-initiating cell maintenance in chronic myeloid leukemia (CML) through its association with the FOXO pathway and activation of Akt signaling (Naka et al 2010;Miyazono 2012).…”
Section: Tgf-b Action In Cancer Stem-cell Maintenancementioning
confidence: 99%